Níveis de autocompaixão e gratidão em pacientes com transtorno por uso de substâncias - Souza, Karine Ranzi Valentim de (2021)
This dissertation was presented in two parts: an empirical article and a psychoeducational booklet. The first aimed to identify the levels of Self-Compassion and Gratitude in adults diagnosed with Substance Use Disorder, correlating them with each other and with symptoms of anxiety, depression and stress, through a descriptive, quantitative and cross-sectional study with 65 adults. For this, a sociodemographic and health questionnaire, the Questionnaire for Screening the use of alcohol, tobacco and other substances (ASSIST), the Gratitude Scale (G20), the Self-Compassion Scale (EAC) and the Depression, Anxiety and Stress - short version (DASS-21). It was concluded that the participants showed high levels of Gratitude, being related to the fact that more than 50% reported being abstinent, and a low level of SelfCompassion. The presence of significant associations between the levels of Self-Compassion and Gratitude was identified, as well as an inverse relationship with the symptomatology: the more grateful and self-compassionate, the less symptoms of depression, anxiety, stress were manifested. Therefore, Positive Psychology can assist in maintaining abstinence. The psychoeducational booklet was produced with the aim of adding knowledge about these strategies to patients, family members, health professionals and other interested parties. In it, exercises were shown to practice gratitude and self-compassion, as well as theoretical aspects explaining the relationship between such variables in a simplified way.